Exploring Challenges in PhD Studies: A Case of Science Student - Abiddin, Norhasni Zainal (EDUCARE, 2008)
ABSTRACT: PhD students have to take responsibility managing their own learning and getting a PhD. They are also responsible for determining what is required as well as for carrying it out, and must always keep in touch in regular meetings with the supervisor. The student is the main person responsible for his/her PhD research. Doing a PhD clearly indicates that this is a studentâs own research and work. The objective of this research is to provide better guidelines for effective roles of a PhD science student, especially the foreign student. The actual research to be reported used the case study method. Three Malaysian PhD students from three major disciplines of study i.e. arts, science and social science, were interviewed in depth several times within a year. All three case studies would make the present article too long. Therefore, only one case study which focusing on science student will be presented in this article in order to achieve a better understanding of the story. As a result, the research had developed the best effective guidelines in order for students to success in their study.KEY WORDS: foreign student, PhD research student, and roles of supervision in the university.About the Author: Dr. Norhasni Zainal Abiddin is a lecturer at the Department of Professional Development and Continuing Education, Faculty of Educational Studies, Universiti Putra Malaysia (UPM). She could be reached at: nonie@ace.upm.edu.myHow to cite this article? Abiddin, Norhasni Zainal. (2008). âExploring Challenges in PhD Studies: A Case of Science Studentâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.103-116. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 9, 2008); Revised (July 10, 2008); and Published (August 17, 2008).